Προσδιορισμός δεικτών για το βοτανικό και γεωγραφικό διαχωρισμό των Κυπριακών Ελαιολάδων - Κρητιώτη, Αγγελίνα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
The effects of the geographical region and the botanical origin of olive oils on the profile of fatty acids, volatile compounds and antioxidants, isolated from monovarietal virgin olive oils from Cyprus were investigated in order to establish for the first time, promising models for authentication and classification of monovarietal virgin olive oils produced on the island. The two dominant Cypriot olive cultivars, Cypriot (ladoelia), and Koroneiki (lianolia), were analyzed for fatty acid composition by GC/FID and volatile compounds were determined by HS-SPME, GC/MS Analysis. Folin-Ciocalteau and DPPH methods were used for total phenol content determination and antiradical activity respectively. The data obtained were analyzed statistically using multivariate and univariate ANOVA, PCA, Hierarchical Cluster Analysis and LDA. Results showed that the olive oils can be separated into two distinct groups using the FAME data bank obtained from 225 samples. Furthermore, significant differences in the concentrations of some volatile compounds from oils of different varieties and geographical regions were detected. The altitude where olive trees are cultivated seems to strongly affect the total phenol content, therefore the susceptibility of olive oil to autoxidation. This is the firt time the Cypriot virgin olive oils are separated according to their botanical origin based on the profile of the fatty acids. Also, new markers have been determined among the volatile components owning stong discriminant power, classifying the virgin olive oils according to variety and to the altitude where olive trees were cultivated.
Keywords: Cypriot virgin olive oil; FAME; Volatiles; Antioxidants; GC-MS; GC-FID; Folin – Ciocalteau; DPPH; Monovarietal; Chemometrics; Altitude; Microclimate; Κυπριακό παρθένο ελαιόλαδο; Λιπαρά οξέα; Πτητικά συστατικά; Αντιοξειδωτικά; Μονοποικιλιακά; Χημειομετρία; Υψόμετρο; Μικρόκλιμα